Rationaliy and Utility of Evaluation Reseach in Policy Making - Lake, Anda (Studies of Transition States and Societies, 2011)
In this article, the author explores the issues associated with the practical signiﬁ cance of evaluation research in the policy making environment of Latvia. Sporadic, selective and rare use of the results of evaluation research is viewed as the central issue of the paper. The objective of this article is to reveal the connection between the action strategy of the groups involved in the implementation of evaluation research and manifestations of practical signiﬁ cance of evaluation. Implementation, utilisation and practical importance of evaluation research are examined not only in relation to rational action strategies of the groups, but also in relation to the understanding of the concept of practical signiﬁ cance of evaluation research. The theoretical framework of the article is based on the conceptual understanding of J. Habermas’ purposive rationality and communicative rationality, as well as C. H. Weiss’ understanding of practical utilisation of evaluation (the instrumental and enlightened models). The practical importance of evaluation research as well as action strategies of implementing evaluation research are studied empirically in the form of qualitative interviews. The author concludes that the rational action strategy (typical of the Latvian policy making environment) of the groups involved in evaluation is not readily compatible with the evaluation approach that focuses on practical utilisation. The lack of communicative rationality in the action strategy of the interacting and involved groups substantially diminishes the role of evaluation research in the identiﬁcation and implementation of the most eﬀective models of solving social issues in policy making in Latvia.